(untitled) (Clinics, 2007)
PURPOSE: Cecal ligation and puncture (CLP) has been used as a useful model for the induction of polymicrobial sepsis. Necrotic tissue resection and peritoneal lavage (REL) are the surgical procedures for controlling perforated appendicitis. The aim of this study was to evaluate leukocyte-endothelial interactions in the rat mesentery in vivo after CLP and REL. METHODS: Thirty-seven male Wistar rats (250-300 g) underwent laparotomy and were randomly assigned to the following groups: 1) SHAM; 2) CLP: animals submitted to CLP, 3) CLP+REL: animals submitted to CLP and REL. Mesenteric leukocyte-endothelial interactions were studied by intravital microscopy assessed once in each animal (3-5 postcapillary venules, 15-25 µm diameter) 24 hours after intervention. Follow-up was performed in all animals; this included analysis of glycemia, lactate, hematocrit, white blood cell count as well as a functional score that was the sum of scoring on the following parameters: alertness, mobility, piloerection, diarrhea, encrusted eyes, and dirty nose and tail. RESULTS: None of the animals showed significant changes in body weight (265 ± 20 g) or in hematocrit levels (46% ± 2%) during the experimental protocol. Compared to SHAM animals, CLP animals showed an increased number of rolling (2x), adherent, and migrating leukocytes (7x) in the mesenteric microcirculation, an increase in blood glucose (136 ± 8 mg/dL), lactate (3.58 ± 0.94 mmol/L), white cell count (23,570 ± 4,991 cells/mm³) and functional alterations (score 11 ± 1), characterized by impaired alertness and mobility, and presence of piloerection, diarrhea, encrusted eyes, and dirty nose and tail. The REL procedure normalized the number of rolling, adherent, and migrated leukocytes in the mesentery; glycemia; lactate; and white blood cell count. The REL procedure also improved the functional score (7 ± 1). CONCLUSION: Local and systemic inflammation was induced by CLP, while REL completely overcame the inflammatory process.